Convergences of thought between Martha Nussbaum, Michel Foucault and Friedrich Schiller (Revista Científica Compendium, 2024)
It is presented an essay focused mainly on the thought of the American philosopher Martha Nussbaum's thought on emotions, aspirational society and human development. Following an exercise of imaginary debate between this intellectual and her colleagues Michel Foucault and Friedrich Schiller, which connects the latter´s aesthetics of human existence with Nussbaumnian philosophy, the role of emotions in the construction of an aspirational society and democracy, the only system that offers real possibilities for human development, is critically addressed.
Keywords: Emotions; aspirational society; aesthetics of existence; democracy; Martha Nussbaum